Expanding mobile wireless capacity: The challenges presented by technology and economics - Richard N. Clarke (International Telecommunications Society (ITS), 2012)
As demand for mobile broadband services continues to explode, mobile wireless networks must expand greatly their capacities. This paper describes and quantifies the economic and technical challenges associated with deepening wireless networks to meet this exploding demand. Methods of capacity expansion divide into three general categories: the deployment of more radio spectrum; more intensive geographic reuse of spectrum; and increasing the throughput capacity of each MHz of spectrum within a given geographic area. The paper first provides a brief technical background on mobile wireless networks and these basic methods to deepen their capacity. It goes on to measure the contribution of each of these methods to historical capacity growth within U.S. networks. The paper then describes the capabilities of 4G LTE wireless technology, and further innovations off of it, to increase network capacity. The capacity expansion capability of LTE-Advanced along with traditional spectrum reuse are quantified, and are compared to forecasts of future demand to evaluate the ability of U.S. networks to match this future demand. We find that without significantly increased allocations of spectrum, wireless capacity expansion will be wholly inadequate to accommodate expected demand growth. This conclusion is in contrast to those that claim that the U.S. faces no spectrum shortage.
Keywords: 330